The Series Bridge Converter (SBC): a hybrid modular multilevel converter for HVDC applications - Amankwah, Emmanuel K.; Costabeber, Alessando; Watson, Alan James; Trainer, David; Jasim, Omar; Chivite-Zabalza, Javie; Clare, Jon C. (2016)
This paper presents a novel hybrid modular multilevel voltage source converter suitable for HVDC applications. It has the advantages of other modular multilevel topologies and can be made more compact making it attractive for offshore stations and city infeed applications. The Operating principle of the converter and internal energy management are discussed with simulation results from a scaled medium voltage demonstrator presented to validate the concepts.